Information communication technologies and the virtual public sphere impact of network structures on civil society - Cropf, Robert A.; Krummenacher, William S., 1975-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book demonstrates how the virtual public sphere uses information communications technology to empower ordinary citizens to engage in effective public discourse and provide the technological means to effect political change"--Provided by publisher.
1. Introduction / Robert Cropf, Scott Krummenacher -- 2. Deliberative machines in techno-political arrangements / Laurence Monnoyer-Smith -- 3. Communicative mechanisms of governance / Lori Anderson, Patrick Bishop -- 4. Habermas, networks and virtual public spheres / Veena Raman -- 5. Issues of digital disempowerment and new media networking (NMN) in relation to E-government / Kenneth Hacker, Eric Morgan -- 6. 'Videoblogging' human rights on YouTube / Jacques Gimeno, Bradley Freeman -- 7. Conceptualizing E-participation in the public sphere / Jenny Backhouse -- 8. An investigation of the use of computer supported arguments visualization for improving public participation in legislation formation / Euripidis Loukis, Alexander Xenakis, Nektaria Tserpeli -- 9. The role of trust in the global acceptance of E-government / John Burbridge, Jayoti Das, Cassandra DiRienzo -- 10. Perspectives on E-government in Europe / Sylvia Archmann, Just Iglesias -- 11. Exploring the ICT capabilities of civil society in Sub Saharan Africa / Joshua Nyirenda -- 12. Setting the foundation for E-democracy in Botswana / Kelvin Bwalya, Tanya Du Plessis, Chris Rensleigh -- 13. Challenges of E-disclosure in Romanian local public authorities / Adriana Tudor, Adina Popa, Rodica Blidisel -- 14. Making room for E-government through succession planning / Kim Loutzenhiser.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed May 4, 2011).
Keywords: Internet in public administration; Political participation -- Technological innovations; Information technology -- Political aspects; Blended deliberative models; E-communicative mechanisms of government; E-financial reporting; E-participation in the public sphere; Factors affecting E-participation adoption; Global E-government and trust; Online public debate; Perspectives on E-government in Europe; Succession planning and E-government; Video blogging and ethics; Electronic books